2018
DOI: 10.1155/2018/6452402
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid Cyst of the Adrenal Gland: Is Radical Surgery Necessary for Recurrent Hydatid Disease?

Abstract: Hydatid cyst disease caused by E. granulosus is a zoonotic disease that may involve many body tissues and organs, mainly liver. Adrenal glands are rarely involved even in regions where hydatid cyst disease is endemic. A limited number of studies have been reported on adrenal gland involvement by hydatid cyst disease. Herein, we aimed to report a recurrent case of adrenal hydatid cyst that was misdiagnosed as a hepatic hydatid cyst. A 16-year-old boy with a history of partial cyst excision and evacuation for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The third point that we would like to emphasize is about the errors regarding the ages and gender of the patients given in Table-1. The study by Akbulut and colleague [ 4 ] reported a patient who was 16 years old but was stated as 64 years old in the Table-1. On the contrary, the study by Seidel and colleagues [ 5 ] states that the patient was 64 years old but was reported as 16 years old in Table-1.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The third point that we would like to emphasize is about the errors regarding the ages and gender of the patients given in Table-1. The study by Akbulut and colleague [ 4 ] reported a patient who was 16 years old but was stated as 64 years old in the Table-1. On the contrary, the study by Seidel and colleagues [ 5 ] states that the patient was 64 years old but was reported as 16 years old in Table-1.…”
mentioning
confidence: 99%
“…In the study by Zouari and colleagues and also other researchers, there is no clear message to give the readers regarding the treatment of AHC disease. In our experience, the treatment of AHC is determined by factors such as the presence of other organs of interest that is affected by the hydatid disease, the size of the AHCs, the involvement of the adjacent organs, radiologic stage, and the complications of the AHC disease (such as rupture, fistulization, hypertension, pheochromocytoma and related symptoms) [ 4 , 9 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations